High-reflection environment-friendly self-cleaning coating for tunnel and preparation method thereof

By using a highly reflected and environmentally friendly self -cleaning paint consisting of a variety of chemicals, the problem of difficulty self -cleaning in the inner wall coatings of the tunnel under the action of oily pollutants, realizing the high reflection and good light environment of the inner wall of the tunnel, reducing Turnive safety hazards and the effect of energy saving and emission reduction.

CN119350960APending Publication Date: 2025-01-24GUIZHOU EXPRESSWAY IND CO LTD GUIYANG BRANCH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411611526.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing tunnel inner wall coating is difficult to clean itself under the action of oily pollutants, resulting in a decrease in the reflection coefficient of the tunnel inner wall, a deterioration of the light environment, and an increase in traffic safety hazards.

Method used

It adopts an February cinnamic acid diexyl tin, end hydroxyl hydrogenation polyphonohne, 4-benzylisocyanate, cyclone, 3-methyl-1,5-pentaol, amino single-sealing end polymond metrophic diexyl-based basis High reflection and environmentally friendly self -clean coatings made of silicide, tetharine gyrolylamine, sulfate wood, and methanes made of methanes.

Benefits of technology

The coating formed on the surface of the tunnel has the advantages of high reflection, ultra -hydrophobic, high oil sparse, strong flame retardant, fluoride -free environmental protection, etc., which can increase the brightness of the tunnel, reduce power consumption, and achieve the effect of energy saving and emission reduction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-reflection environment-friendly self-cleaning coating for tunnels, which is mainly prepared from the following materials in parts by weight: 4-6 parts of dioctyl tin dilaurate, 40-50 parts of hydroxyl-terminated hydrogenated polyisoprene, 90-110 parts of 4-phenyl isocyanate, 100 parts of cyclohexanone, 10 parts of 3-methyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3, 4-trimethyl-1, 3-trimethyl-1 The invention relates to a high-temperature-resistant silicone sealant, which is prepared from the following components in parts by weight: 50 to 60 parts of 1, 5-pentanediol, 4 to 5 parts of amino single-terminated polydimethylsiloxane, 15 to 20 parts of tetraethylenepentamine and 15 to 20 parts of copolymer of sulfate lignin and methyl silsesquioxane. The invention provides the high-reflection environment-friendly self-cleaning coating for the tunnel. A coating formed on the surface of a tunnel has the advantages of high reflection, super-hydrophobicity, high oleophobicity, strong flame retardance, fluoride-free environment friendliness and the like, and when the coating is used for coating the inner wall of the tunnel, the brightness in the tunnel can be improved for a long time, the power consumption is reduced, and the effects of energy conservation and emission reduction are achieved. The invention also provides a preparation method of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of public safety technology, in particular to the field of road engineering technology, and specifically to a highly reflective, environment-friendly, self-cleaning coating for improving the light environment in a tunnel and a preparation method thereof. Background Art

[0002] In order to ensure the safety of the main structure of the tunnel in a fire environment, the inner wall of the existing tunnel is usually painted with fire retardant coatings. At present, the fire retardant coatings used in domestic highway tunnel projects must meet the requirements of "Highway Engineering-Tunnel Fire Retardant Coatings" (JT / T 1308-2020).

[0003] Due to the large difference in brightness inside and outside the tunnel, it is very easy to form a "black hole effect" and a "white hole effect", which poses a great safety hazard to passing vehicles. Therefore, in addition to the technical requirements of "Highway Engineering-Tunnel Fire Retardant Coating" (JT / T 1308-2020), researchers have also studied the optical properties of tunnel inner wall coatings. For example, the technical solution of the construction method of a tunnel fire retardant coating in Chinese patent CN113217077A can be within 60 meters of the tunnel entrance. The luminous intensity of the coating changes according to the intensity of the light to reduce the brightness difference inside and outside the tunnel and eliminate the black hole and white hole phenomenon in the tunnel; the coating in the middle section of the tunnel has luminescence and negative ion functions, so that the tunnel can be continuously illuminated. The technical solution provided by Chinese patent CN112280418A A diffuse reflection tunnel fire retardant coating and construction method can also effectively improve the brightness in the tunnel by using the tunnel wall to reflect the light back and forth multiple times without adding the original lamps in the tunnel.

[0004] However, for highway tunnels, due to the long-term accumulation of automobile exhaust in the tunnel, the hydrocarbon oily mixture emitted by automobile exhaust and dust are combined with each other, which easily forms black oily composite pollutants, adheres to the inner wall of the tunnel, and is extremely difficult to clean, resulting in the inner wall of the tunnel being black and gray, which not only reduces the quality of the tunnel traffic environment, but also causes the reflection coefficient of the inner wall coating of the tunnel to decrease, thereby causing the light environment in the tunnel to deteriorate, causing traffic safety accidents. In the prior art, hydrophobic coatings are mostly used on the inner wall of the tunnel in order to achieve the purpose of self-cleaning and easy cleaning. However, oily pollutants are mainly present in highway tunnels. Since the surface tension of oil is much higher than that of water, the requirements of oleophobic coatings on surface energy are more stringent. Although some self-cleaning coatings have shown good hydrophobic properties, they still need to be further improved in terms of oleophobicity, and it is difficult to achieve self-cleaning coating of the inner wall of the tunnel. Fluoride has extremely low surface energy, and some technologies improve the oleophobic ability of the coating by introducing fluorinated compounds. However, fluoride is expensive and harmful to both the human body and the environment. At the same time, the tunnel is a closed environment. In order to meet the fire protection requirements and improve the overall lighting environment in the tunnel, the self-cleaning coating must also have a high reflectivity and good flame retardant effect. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a highly reflective, environmentally friendly, self-cleaning coating for tunnels to reduce or avoid the above-mentioned problems. The present invention also provides a method for preparing the coating.

[0006] The invention provides a highly reflective, environment-friendly self-cleaning coating for a tunnel. The coating is mainly made of the following materials in parts by weight: 4-6 parts of dioctyltin dilaurate, 40-50 parts of terminal hydroxyl hydrogenated polyisoprene, 90-110 parts of 4-phenyl isocyanate, 100 parts of cyclohexanone, 50-60 parts of 3-methyl-1,5-pentanediol, 4-5 parts of amino mono-terminated polydimethylsiloxane, 15-20 parts of tetraethylenepentamine, and 15-20 parts of a copolymer of sulfate lignin and methyl silsesquioxane.

[0007] Preferably, the purity of the dioctyltin dilaurate is not less than 98%.

[0008] Preferably, the average molecular weight of the hydroxy-terminated hydrogenated polyisoprene is 2400-2600.

[0009] Preferably, the purity of the 4-phenylisocyanate is not less than 99.5%.

[0010] Preferably, the purity of cyclohexanone is not less than 99%.

[0011] Preferably, the purity of the 3-methyl-1,5-pentanediol is not less than 97%.

[0012] Preferably, the amino mono-terminated polydimethylsiloxane has a purity of not less than 99%.

[0013] Preferably, the tetraethylenepentamine has a purity of not less than 98%.

[0014] Preferably, the copolymer of kraft lignin and methyl silsesquioxane is prepared by the following method: S1. Adding the kraft lignin particles to the methylsilsesquioxane solution and stirring evenly by magnetic force; S2. The pH value of the solution is adjusted to between 10 and 12 using sodium hydroxide; S3. The solution was heated to 60°C for 48 hours; S4. The reaction product was centrifuged, the supernatant of the solution was added to deionized water, and the pH of the solution was adjusted to 6.5-7.5 using hydrochloric acid; S5. After dialyzing the solution for 24 hours, the solution was placed in a standard oven at 60° C. and dried for not less than 48 hours to obtain a copolymer of sulfate lignin and methyl silsesquioxane.

[0015] The present invention also provides a method for preparing the above coating, which comprises the following steps: S1. In a nitrogen environment at 80°C, using dioctyltin dilaurate as a catalyst, hydroxy-terminated hydrogenated polyisoprene and 4-phenylisocyanate were added to a cyclohexanone solution for addition polymerization for 2 hours; S2. Add 3-methyl-1,5-pentanediol and continue the reaction for 6 hours; S3. After the solution cools to room temperature, the solvent is filtered so that the solid content in the solution is 10%; S4. Add amino mono-terminated polydimethylsiloxane, tetraethylenepentamine, sulfate lignin and methyl silsesquioxane copolymer, and stir evenly by magnetic force; complete the coating preparation.

[0016] The highly reflective and environment-friendly self-cleaning coating for tunnels provided by the present invention has the advantages of high reflectivity, super hydrophobicity, high oleophobicity, strong flame retardancy, fluorine-free and environment-friendly, etc. When used for coating the inner wall of a tunnel, it can improve the brightness in the tunnel for a long time, reduce power consumption, and achieve the effect of energy saving and emission reduction. The present application also provides a method for preparing the coating. DETAILED DESCRIPTION

[0017] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, this application uses five specific embodiments and four comparative examples to illustrate the beneficial effects of the present invention through data comparison.

[0018] Specifically, the present invention provides a highly reflective, environmentally friendly, self-cleaning coating for tunnels, which is mainly made of the following materials in parts by weight: 4-6 parts of dioctyltin dilaurate, 40-50 parts of terminal hydroxyl hydrogenated polyisoprene, 90-110 parts of 4-phenyl isocyanate, 100 parts of cyclohexanone, 50-60 parts of 3-methyl-1,5-pentanediol, 4-5 parts of amino mono-terminated polydimethylsiloxane, 15-20 parts of tetraethylenepentamine, and 15-20 parts of a copolymer of sulfate lignin and methyl silsesquioxane.

[0019] The purity of the dioctyltin dilaurate is not less than 98%, the average molecular weight of the terminal hydroxyl hydrogenated polyisoprene can be 2400-2600, the purity of the 4-phenylisocyanate is not less than 99.5%, the purity of the cyclohexanone is not less than 99%, the purity of the 3-methyl-1,5-pentanediol is not less than 97%, the purity of the amino mono-terminated polydimethylsiloxane is not less than 99%, and the purity of the tetraethylenepentamine is not less than 98%.

[0020] The copolymer of kraft lignin and methyl silsesquioxane can be prepared by the following method: S1. Adding the kraft lignin particles to the methylsilsesquioxane solution and stirring evenly by magnetic force; S2. The pH value of the solution is adjusted to between 10 and 12 using sodium hydroxide; S3. The solution was heated to 60°C for 48 hours; S4. The reaction product was centrifuged, the supernatant of the solution was added to deionized water, and the pH of the solution was adjusted to 6.5-7.5 using hydrochloric acid; S5. After dialyzing the solution for 24 hours, the solution was placed in a standard oven at 60° C. and dried for not less than 48 hours to obtain a copolymer of sulfate lignin and methyl silsesquioxane.

[0021] In the preparation process of the copolymer of kraft lignin and methyl silsesquioxane, the kraft lignin can be coniferous wood lignin or broadleaf wood lignin, with a particle size of 5-20 μm, a water content of less than 5%, and an effective component of not less than 90%. The mass ratio of the kraft lignin to the methyl silsesquioxane can be 1:1.0-1.3. The purity of the methyl silsesquioxane is not less than 99%, the concentration of the sodium hydroxide can be 1 mol / L, and the concentration of the hydrochloric acid can be 1 mol / L.

[0022] In S4, the mass ratio of the supernatant to the deionized water may be 1:1.8-2.

[0023] The material components of the five specific embodiments and four comparative examples recorded in this application are shown in the following table: Material composition Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Dioctyltin dilaurate 4.5 servings 4.5 servings 5 servings 5 servings 5.5 servings 4.5 servings 4.5 servings 4.5 servings 4.5 servings Hydroxyl-terminated hydrogenated polyisoprene 40 servings 45 servings 45 servings 50 servings 45 servings 40 servings 40 servings 20 servings 40 servings 4-Phenyl isocyanate 90 servings 95 copies 90 servings 100 copies 95 copies 90 servings 90 servings 30 servings 50 servings Cyclohexanone 100 copies 100 copies 100 copies 100 copies 100 copies 100 copies 100 copies 100 copies 100 copies 3-Methyl-1,5-pentanediol 50 servings 60 servings 55 servings 50 servings 55 servings 50 servings 50 servings 50 servings 20 servings Amino-terminated polydimethylsiloxane 5 servings 4.5 servings 4 servings 4.5 servings 5 servings 5 servings 0 copies 5 servings 5 servings Tetraethylenepentamine 20 servings 15 servings 15 servings 20 servings 15 servings 20 servings 0 copies 20 servings 20 servings Copolymer of kraft lignin and methyl silsesquioxane 15 servings 20 servings 15 servings 20 servings 15 servings 0 copies 5 servings 15 servings 15 servings The material properties listed in the above table are described in detail below.

[0024] The purity of the dioctyltin dilaurate is 99%, the average molecular weight of the terminal hydroxyl hydrogenated polyisoprene is 2500, the purity of the 4-phenylisocyanate is 99.5%, the purity of the cyclohexanone is 99%, the purity of the 3-methyl-1,5-pentanediol is 98%, the purity of the amino mono-terminated polydimethylsiloxane is 99%, and the purity of the tetraethylenepentamine is 98%.

[0025] The copolymer of kraft lignin and methyl silsesquioxane is prepared by the following method: S1. Adding the kraft lignin particles to the methylsilsesquioxane solution and stirring evenly by magnetic force; S2. The pH value of the solution was adjusted to 11 using sodium hydroxide; S3. The solution was heated to 60°C for 48 hours; S4. The reaction product was centrifuged, the supernatant of the solution was added to deionized water, and the pH of the solution was adjusted to 7 using hydrochloric acid; S5. The solution was dialyzed for 24 hours and then dried in a standard oven at 60° C. for 48 hours to obtain a copolymer of sulfate lignin and methyl silsesquioxane.

[0026] In the preparation process of the copolymer of kraft lignin and methyl silsesquioxane, the purity of the methyl silsesquioxane is 99.5%, the concentration of the sodium hydroxide is 1 mol / L, and the concentration of the hydrochloric acid is 1 mol / L.

[0027] In S4, the mass ratio of the supernatant to deionized water is 1:2.

[0028] In order to compare the performance differences brought by different commercially available materials, the kraft lignin in Examples 1, 3, 5 and Comparative Examples 2 to 4 uses coniferous wood lignin, with a particle size between 5 and 20 μm, a moisture content of less than 5%, and an effective component of 90%. The kraft lignin in Examples 2, 4 and Comparative Example 1 uses broadleaf wood lignin, with a particle size between 5 and 20 μm, a moisture content of less than 5%, and an effective component of 90%.

[0029] In addition, in the preparation process of the copolymer of kraft lignin and methyl silsesquioxane, in Examples 1, 3, 5 and Comparative Examples 1 to 4, the mass ratio of kraft lignin to methyl silsesquioxane is 1:1.1. In Examples 2 and 4, the mass ratio of kraft lignin to methyl silsesquioxane is 1:1.3.

[0030] The highly reflective, environment-friendly, self-cleaning coatings for tunnels provided in Examples 1 to 5 and Comparative Examples 1 to 4 can be prepared by the following method: S1. In a nitrogen environment at 80°C, using dioctyltin dilaurate as a catalyst, hydroxy-terminated hydrogenated polyisoprene and 4-phenylisocyanate were added to a cyclohexanone solution for addition polymerization for 2 hours; S2. Add 3-methyl-1,5-pentanediol and continue the reaction for 6 hours; S3. After the solution cools to room temperature, the solvent is filtered so that the solid content in the solution is 10%; S4. Add amino mono-terminated polydimethylsiloxane, tetraethylenepentamine, sulfate lignin and methyl silsesquioxane copolymer, and stir evenly by magnetic force; the coating preparation is completed.

[0031] After the coating is prepared, when the coating is prepared as a coating on a concrete structure (such as the inner wall of a tunnel), the following operations need to be performed: ultrasonic defoaming of the coating solution is performed, and the coating is prepared on the surface of the concrete structure using ultrasonic jet deposition technology. The ultrasonic jet deposition technology is to use compressed air with a flow rate of 9 to 11 ml / min as a carrier gas, spray on the surface of the structure at a frequency of 1.7 to 1.9 MHz, and the distance between the nozzle and the coating surface is 4 to 6 cm.

[0032] Specifically, when the coatings produced by the five specific embodiments and four comparative examples in this application are prepared as coatings on the concrete surface, the ultrasonic jet deposition technology is to use compressed air with a flow rate of 10 ml / min as the carrier gas, spray on the surface of the concrete structure at a frequency of 1.8 MHz, and the distance between the nozzle and the coating surface is 5 cm.

[0033] After the coatings produced in the five specific embodiments and four comparative examples of the present invention were prepared as coatings on the concrete surface, water contact angle, oil contact angle and reflection coefficient were tested, and combustion performance was tested according to the Classification of Combustion Performance of Building Materials and Products (GB8624-2006). The results are shown in the following table: Test items Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Water contact angle (°) 158 151 154 151 156 153 146 142 138 Oil contact angle (°) 142 138 133 135 145 136 123 129 125 Reflection coefficient (%) 88.3 85.5 86.1 87.2 83.8 82.4 78.2 76.3 78.3 Combustion level A1 A1 A1 A1 A1 A2 A2 A1 A1 It can be seen from the test data recorded in the above table that, compared with Comparative Examples 1 to 4, the coating prepared by the coating obtained in Examples 1 to 5 has the advantages of high reflection, super hydrophobicity, high oleophobicity, strong flame retardancy, fluorine-free and environmentally friendly, the water contact angle reaches more than 150°, and the oil contact angle reaches more than 130°, so it has excellent self-cleaning properties. In addition, the reflection coefficient reaches more than 83%, and the combustion grade reaches A1. When used for coating the inner wall of a tunnel, it can long-term improve the brightness in the tunnel, reduce power consumption, and achieve the effect of energy saving and emission reduction.

[0034] The highly reflective and environment-friendly self-cleaning coating for tunnels provided by the present invention has the advantages of high reflectivity, super hydrophobicity, high oleophobicity, strong flame retardancy, fluorine-free and environment-friendly, etc. When used for coating the inner wall of a tunnel, it can improve the brightness in the tunnel for a long time, reduce power consumption, and achieve the effect of energy saving and emission reduction. The present application also provides a method for preparing the coating.

[0035] Those skilled in the art should understand that although the present invention is described in the form of multiple embodiments, not every embodiment includes only one independent technical solution. Such description in the specification is only for the sake of clarity. Those skilled in the art should understand the specification as a whole and regard the technical solutions involved in each embodiment as being able to be combined into different embodiments to understand the scope of protection of the present invention.

[0036] The above description is only an illustrative embodiment of the present invention and is not intended to limit the scope of the present invention. Any equivalent changes, modifications and combinations made by any person skilled in the art without departing from the concept and principle of the present invention shall fall within the scope of protection of the present invention.

Claims

1. A highly reflective, environmentally friendly, self-cleaning coating for tunnels, characterized in that: The invention is mainly made of the following materials in parts by weight: 4-6 parts of dioctyltin dilaurate, 40-50 parts of terminal hydroxyl hydrogenated polyisoprene, 90-110 parts of 4-phenyl isocyanate, 100 parts of cyclohexanone, 50-60 parts of 3-methyl-1,5-pentanediol, 4-5 parts of amino mono-terminated polydimethylsiloxane, 15-20 parts of tetraethylenepentamine, and 15-20 parts of a copolymer of sulfate lignin and methyl silsesquioxane.

2. The coating according to claim 1, characterized in that The purity of the dioctyltin dilaurate is not less than 98%.

3. The coating according to claim 1, characterized in that The average molecular weight of the terminal hydroxyl hydrogenated polyisoprene is 2400-2600.

4. The coating according to claim 1, characterized in that The purity of the 4-phenyl isocyanate is not less than 99.5%.

5. The coating according to claim 1, characterized in that The cyclohexanone purity is not less than 99%.

6. The coating according to claim 1, characterized in that The purity of the 3-methyl-1,5-pentanediol is not less than 97%.

7. The coating according to claim 1, characterized in that The amino mono-terminated polydimethylsiloxane has a purity of not less than 99%.

8. The coating according to claim 1, characterized in that The purity of the tetraethylenepentamine is not less than 98%.

9. The coating according to claim 1, characterized in that The copolymer of kraft lignin and methyl silsesquioxane is prepared by the following method: S1. Adding the kraft lignin particles to the methylsilsesquioxane solution and stirring evenly by magnetic force; S2. The pH value of the solution is adjusted to between 10 and 12 using sodium hydroxide; S3. The solution was heated to 60°C for 48 hours; S4. The reaction product was centrifuged, the supernatant of the solution was added to deionized water, and the pH of the solution was adjusted to 6.5-7.5 using hydrochloric acid; S5. After dialyzing the solution for 24 hours, the solution was placed in a standard oven at 60° C. and dried for not less than 48 hours to obtain a copolymer of sulfate lignin and methyl silsesquioxane.

10. A method for preparing a coating according to any one of claims 1 to 9, characterized in that: It includes the following steps, S1. In a nitrogen environment at 80°C, using dioctyltin dilaurate as a catalyst, hydroxy-terminated hydrogenated polyisoprene and 4-phenylisocyanate were added to a cyclohexanone solution for addition polymerization for 2 hours; S2. Add 3-methyl-1,5-pentanediol and continue the reaction for 6 hours; S3. After the solution cools to room temperature, the solvent is filtered so that the solid content in the solution is 10%; S4. Add amino mono-terminated polydimethylsiloxane, tetraethylenepentamine, sulfate lignin and methyl silsesquioxane copolymer, and stir evenly by magnetic force; complete the coating preparation.

Citation Information

Patent Citations

  • Diffuse reflection tunnel fireproof coating and construction method

    CN112280418A

  • Construction method of tunnel fireproof coating

    CN113217077A

  • Organic silicon coating as well as preparation method and application thereof

    CN113322000A

  • Two-component polyurethane waterproof coating and preparation method thereof

    CN117467345A

  • Biomass-based waterborne polyurethane, preparation method of textile and leather

    CN117946366A